Progression of early repolarization patterns at a four year follow‐up in a female flight crew population: Implications for aviation medicine. Issue 6 (30th May 2017) - Rohel, Gwénolé; Perrier, Eric; Delluc, Aurélien; Monin, Jonathan; Manen, Olivier; Paule, Philippe; Piquemal, Marie; Mansourati, Jacques; Vinsonneau, Ulric
Abstract : Background: To assess the prevalence, the appearance, and the distribution, as well as the fluctuation over time of early repolarization patterns after four years in a female population derived from the French aviation sector. Methods: This was a retrospective longitudinal study from 1998 to 2010 of a population of female employees who received a full clinical examination and an electrocardiogram (ECG) upon their recruitment and after a period of four years. Results: A total of 306 women were included (average of 25.87 ± 3.3 years of age). The prevalence of early repolarization was 9.2%. The most common appearance was J‐point slurring for 64.3% (i.e. 20/28 subjects) that occurred in the inferior leads for 28.6% (i.e. 8/28 subjects). After four years, the prevalence was 7.5%, with a regression of this aspect in five of the subjects. There were no changes in the ECG in terms of the distribution and the appearance among the 23 subjects for whom the aspect persisted. Over the course of this four year period all of the subjects remained asymptomatic. Conclusions: Early repolarization in this largely physically inactive female population was common, and it fluctuated over time. At present, no particular restrictions can be placed on asymptomatic flight crew who exhibit this feature in the absence of a prior medical history for heart disease.